Variance and covariance component estimation of reproductive traits in a multibreed beef cattle herd applying linear and threshold models - Van der Westhuizen, Robert Rolfe (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric )--University of Stellenbosch, 2001.